PENERAPAN PASAL 14 MENGENAI KEWAJIBAN IKUT KEPESERTAAN BADAN PENYELENGGARA JAMINAN SOSIAL BERDASARKAN UNDANG-UNDANG NOMOR 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL - Yudgest Beno Eko Saputra (MIH Unsoed, 2018)
This study aims to determine the implementation of the obligation to participate in the Social Security Administering Body Board pursuant to Article 14 of Law Number 24 Year 2011 on the Social Security Administering Body. In addition, to analyze the provision of sanctions to the participants of the Health Insurance Administering Agency that is not orderly in paying dues. To achieve these objectives, the authors use normative juridical methods. The result of the research states that the Implementation of Article 14 concerning the obligation to participate in the membership of the social security organizing body pursuant to Law Number 24 Year 2011 on the Social Security Administering Body is implemented through two presidential regulations namely Presidential Regulation no. 12 Year 2013 on Health Insurance and its amendment and PP. 86 of 2013 on Procedures for Imposing Administrative Sanctions to the Employer Other than the State Operator and any person, other than the employer, the worker and the Beneficiary of the Contribution in the Implementation of Social Security and the regulation of the President of Republic of Indonesia no. 19 of 2016 on the second amandement of presidential regulation n0. 12 of 2013 on health insurance. Health Insurance membership is mandatory and is done gradually to cover the entire population. The first phase begins on January 1, 2014, then the second phase covers all the residents who have not entered as Participants BPJS Health no later than January 1, 2019. Penrakan participants Health Insurance Administering Agency that is not orderly in paying dues done with BPJS benefit activation procedure.